Lexical-Semantic, Linguo-Culturological Study Of Tourism Terms Of The French And Russian Languages - Marupova Gulnoz Umarzhonovna (Indonesian Journal of Innovation Studies, 2022)
Tourism as a phenomenon of civilization, being a modern mass form of travel organization, realizes the needs of the individual associated with the diversification of opportunities and competencies. Communication in the tourism sector creates a discourse that fully reflects the multidimensionality of goals, themes, values and diversity of participants in the interaction processes.